Boys' Club or Good Ol' Boys Club? Corruption and the Parliamentary Representation of Young and Old Men and Women. Issue 2 (13th March 2020) - Stockemer, Daniel; Wigginton, Michael; Sundström, Aksel
Abstract: Research on political representation has shown that corruption is not gender-neutral: it benefits the recruitment of men to political office more than it does women. Yet, it is unclear if all men or a specific type of men, elderly men, benefits the most from corrupt networks in terms of political presence. The 'old boys' network thesis' would single out older men as the most likely beneficiaries of the homosocial capital gained through informal ties in corrupt settings. In this article, we test this thesis based on a dataset comprising 98 national parliaments. Through bivariate and multivariate analyses, we find that corruption tends to benefit the presence of men regardless of their age. We further conjecture that the inclusion of young male patrons into nepotistic and clientelistic networks could further explain why these networks of 'gendered' corruption have been so sticky over time.